THE EFFECT OF USING TYPES OF OIL IN THE RATIONS ON THE CARCASS PIECESOF MALE BALI DUCKS - N. P. R., Pratita; Nuriyasa, I M.; Puger, A. W. (Jurnal Peternakan Tropika, 2021)
This study aims to determine the effect of using types of oil in rations on carcass pieces of male Bali ducks.  This research was conducted in Dajan Peken Village, Tabanan for 10 weeks.  The research design used was a completely randomized design (CRD) consisting of 5 treatments and 4 replications and each replication contained 2 male Balinese ducks with a weight range of 223±19.36 g. The treatment consisted of R0 = use of 0% oil in the ration, R1 = use of 3% palm oil in the ration, R2 = use of 3% fish oil in the ration, R3 = use of 3% used cooking oil in the ration, and R4 = use of 3% pork oil in the ration.  The research rations were given to ducks with a metabolic energy content of 2,900 Kcal / kg and 18% protein. The variables observed were cut weight, carcass weight, carcass percentage, and carcass pieces percentage which included breast, thigh, drumstick, wing and back.  The results showed that the slaughter weight, carcass weight, carcass percentage, and carcass cut percentage were not influenced by the use of palm oil, fish oil, used cooking oil, and pork oil in the ration by 3% compared to the control.  Based on the results of this study it can be concluded that the use of oil with a dose of 3% in the ration has no effect on slaughter weight, carcass weight, carcass percentage, and carcass percentage of male Bali ducks. Keywords: male bali duck, shlaugtered weight, carcass pieces